VD_FINDINFO Jug / 2022 / 478 vom 24. Oktober 2022 - VD Tribunal cantonal (2022)
VIOLATION DES RÈGLES DE LA CIRCULATION, PROCÉDURE ÉCRITE, REJET DE LA DEMANDE | 90 al. 1 LCR, 25 al. 5 OCR, 398 al. 4 CPP (CH)